Multicenter R2* mapping in the healthy brain. Issue 3 (8th May 2013) - Ropele, Stefan; Wattjes, Mike P.; Langkammer, Christian; Kilsdonk, Iris D.; de, Wolter L.; Frederiksen, Jette L; Fuglø, Dan; Yiannakas, Marios; Wheeler‐Kingshott, Claudia A. M.; Enzinger, Christian; Rocca, Maria A.; Sprenger, Till; et al.
<x xml:space="preserve">Abstract</x> Purpose The <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg4sw2zkt9" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />R2*</alternatives> relaxation rate constant has been suggested as a sensitive measure for iron accumulation. The aim of this multi‐center study was to assess the inter‐scanner and inter‐subject variability of <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg4sw2zkqn" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />R2*</alternatives> mapping and to investigate the relationship between brain volume and <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg4sw2zkr6" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />R2*</alternatives> in specific structures. Methods <alternatives> <inline-graphic mimetype="image" xlink:href="ark:/27927/pgg4sw2zkm0" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> R 2 * </alternatives> mapping was performed in 81 healthy subjects in seven centers using different 3 T systems. <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg4sw2zknj" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />R2*</alternatives> was calculated from a dual‐echo gradient echo sequence and was assessed in several deep gray matter structures. The inter‐scanner and inter‐subject variability of <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg4sw2zk8g" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />R2*</alternatives> was calculated by means of the coefficient of variation before and after correcting for age. Results Significant center effects were seen in some regions which get lost after age correction. The coefficient of variation for the inter‐center variability was much lower (<5.6%) than for the intra‐subject variability (6.7%–11.7%). <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg4sw2zk6c" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />R2*</alternatives> in the putamen and red nucleus scaled with cortical volume while <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg4sw2zm5b" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />R2*</alternatives> in the globus pallidus and the substantia nigra was negatively associated with white matter volume. Conclusion <alternatives> <inline-graphic mimetype="image" xlink:href="ark:/27927/pgg4sw2zmb3" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> R 2 * </alternatives> is a robust and reproducible measure in a multicenter setting provided that a standardized MRI protocol is used. The relationship between iron concentration in deep gray matter and volume of specific brain compartments needs further investigation. Magn Reson Med 71:1103–1107, 2014. © 2013 Wiley Periodicals, Inc.